Individual differences in reward prediction error: contrasting relations between feedback-related negativity and trait measures of reward sensitivity, impulsivity and extraversion - Cooper, Andrew J.; Duke, Éilish; Pickering, Alan D.; Smillie, Luke D. (Frontiers in Human Neuroscience, 2014)
Medial-frontal negativity occurring ~200-300 msec post-stimulus in response to motivationally salient stimuli, usually referred to as feedback related negativity (FRN), appears to be at least partly modulated by dopaminergic-based reward prediction error (RPE) signaling. Previous research (e.g. Smillie, Cooper & Pickering, 2011) has shown that higher scores on a putatively dopaminergic-based personality trait, Extraversion, were associated with a more pronounced difference wave contrasting unpredicted non-reward and unpredicted reward trials on an associative learning task. In the current study, we sought to extend this research by comparing how trait measures of Reward Sensitivity, Impulsivity and Extraversion related to the FRN using the same associative learning task. A sample of healthy adults (N = 38) completed a battery of personality questionnaires, before completing the associative learning task while EEG was recorded. As expected, FRN was most negative following unpredicted non-reward. A difference wave contrasting unpredicted non-reward and unpredicted reward trials was calculated. Extraversion, but not measures of Impulsivity, had a significant association with this difference wave. Further, the difference wave was significantly related to a measure of anticipatory pleasure, but not consummatory pleasure. These findings provide support for the existing evidence suggesting that variation in dopaminergic functioning in brain ‘reward’ pathways may partially underpin associations between the FRN and trait measures of extraversion and anticipatory pleasure.